2007
DOI: 10.1897/05-646r1.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the reproductive effects of tamoxifen citrate in partial and full life‐cycle studies using fathead minnows (Pimephales Promelas)

Abstract: Laboratory studies were conducted to investigate potential adverse effects on development, growth, reproduction and biomarker responses (vitellogenin [VTG] and gonad histology) in fathead minnows (Pimephales promelas) exposed to tamoxifen citrate. Based on the results of a partial life cycle study (nominal [mean measured] concentrations ranged from 0.18 [0.11] to 18 [15.74] microg/L), a 284-d fish full life-cycle (FFLC) flow-through study was conducted using newly fertilized embryos (<24 h postfertilization) e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Other researchers have also reported large individual variation in the VTG concentration of control fish [38] and in the VTG response following oestrogen exposure [39]. This variation in plasma VTG concentration between fish seems unlikely to be due to the physiological status of the fish, as all fish within one tank were of the same age and kept under identical conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Other researchers have also reported large individual variation in the VTG concentration of control fish [38] and in the VTG response following oestrogen exposure [39]. This variation in plasma VTG concentration between fish seems unlikely to be due to the physiological status of the fish, as all fish within one tank were of the same age and kept under identical conditions.…”
Section: Discussionmentioning
confidence: 93%
“…Winter et al (2008) reported a 28-day growth NOEC and LOEC for the b 1 -adrenergic receptor antagonist atenolol to be 3.2 and 10 mg/L, respectively. However, decreases in growth during this 28-day study may be transient and not representative of impacts during an entire fish full life cycle (Williams et al 2007).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the anticancer drug tamoxifen citrate interferes with oestrogen signalling, yet a full life cycle (~9 month) exposure at concentrations higher than those typically found in the environment (0.18 μ g L −1 ) did not affect reproduction of fathead minnow (Williams et al . ). Often chemical exposures conducted in the shorter term find effects at concentrations higher than those found in the environment with the suggestion that such exposure regimes are predictive of the effects of longer exposures to lower (environmentally relevant) concentrations.…”
Section: Limitations In Current Methodologies For Assessing Impacts Omentioning
confidence: 97%